A Model of Entrepreneurial Intention Through Behavioral Approaches - Kurjono, Kurjono; Mulyani, Heni; Murtadlo, Yusuf (Fakultas Ekonomi, Universitas Negeri Semarang, 2018)
The purpose of this study was to determine the effect of entrepreneurial attitudes, subjective norms and perceived behaviour control on entrepreneurial intentions both directly and indirectly and to know the differences in entrepreneurial intentions in terms of gender, regional origin, and scientific fields. The research method used was explanatory survey method. The population was 19,919 students with a sample size of 377 respondents. The research sample taken from the UPI student population consisted of 13 sections, faculties and regional campuses. Data collection used a questionnaire that had been tested for validity and reliability. Data processing techniques used descriptive analysis and path analysis. The results showed that entrepreneurial attitudes and control behaviour had a significant positive effect on entrepreneurial intentions. Perceived behaviour control had the greatest influence on entrepreneurial intentions. There was no difference in intention of entrepreneurship from the aspect of gender, as well as students who come from villages and cities, however there were differences in entrepreneurial intentions from the scientific aspects between science and humanities majors. Suggestions from the results of this study were lecturers and educators should maintain an entrepreneurial attitude by increasing indicators of interest in business opportunities.